2019
DOI: 10.4041/kjod.2019.49.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the association between orthodontic treatment and temporomandibular joint pain and dysfunction in the South Korean population

Abstract: Objective This study investigated the relationship between orthodontic treatment and temporomandibular disorders (TMD) in South Korean population. Methods This study obtained data from the 2012 Korean National Health and Nutrition Examination Survey. The final sample size was 5,567 participants who were ≥ 19 years of age. Logistic regression analysis was performed to evaluate the relationship between orthodontic treatment and TMD. Results Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…e time from the first tooth contact to maximum intercuspation during the closing movement is defined as the occlusion time. [26] In our study, it was observed that the occlusion time was 0.33±0.35, 0.28±0.15 ve 0.32±0.20 0.18 s in the T2 time. In addition, no statistically significant difference was observed between the extraction group at T0, T1, and T2, and the non-extraction group, in terms of the occlusion times.…”
Section: Discussionsupporting
confidence: 45%
“…e time from the first tooth contact to maximum intercuspation during the closing movement is defined as the occlusion time. [26] In our study, it was observed that the occlusion time was 0.33±0.35, 0.28±0.15 ve 0.32±0.20 0.18 s in the T2 time. In addition, no statistically significant difference was observed between the extraction group at T0, T1, and T2, and the non-extraction group, in terms of the occlusion times.…”
Section: Discussionsupporting
confidence: 45%
“…Overall, 6 studies ( 20 - 25 ) from 6 different countries were included, of which 4 are case-control, 1 cohort and 1 prospective cohort. One of the most salient features is in relation to the number of patients, with men and women being considered with their respective mean ages and/or according to range.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most salient features is in relation to the number of patients, with men and women being considered with their respective mean ages and/or according to range. Regarding the extraction of results, all 6 studies ( 20 - 25 ) reported the OR and the confidence interval (CI), while only studies 2 and 3 reported the relative risk, therefore, for the meta-analysis, ORs were considered because all of them had this statistical result ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, higher financial costs seem to limit experimentation with non-human primates; additionally, current restrictions imposed by ethics prevent recruiting humans as experimental subjects in interventions that may culminate in irreversible or undesirable outcomes [ 65 ]. There has not been a definitive agreement on the mechanism [ 14 ] and the possible side effects of the most common treatments of developmental deviations [ 43 , 45 , 66 ].…”
Section: Discussionmentioning
confidence: 99%